ChemInform Abstract: Carbon Nanotubes and Catalysis: The Many Facets of a Successful Marriage. Issue 37 (September 2015) - Melchionna, M.; Marchesan, S.; Prato, M.; Fornasiero, P.
Abstract Review: 122 refs.